Different and diverse anaerobic microbiota were seen in women living with HIV with unsuppressed HIV viral load and in women with recurrent bacterial vaginosis: a cohort study. (6th October 2019) - Elwood, C; Albert, AYK; McClymont, E; Wagner, E; Mahal, D; Devakandan, K; Quiqley, BL; Pakzad, Z; Yudin, MH; Hill, JE; Money, D; ,
Abstract : Objective: To compare the vaginal microbiota of women living with HIV (WLWH) with the vaginal microbiota of women with recurrent bacterial vaginosis (BV) and healthy women without HIV to determine if there are differences in the vaginal microbiome, what factors influence these differences, and to characterise HIV clinical parameters including viral load and CD4 count in relation to the vaginal microbiome. Design: Observational cohort study. Setting: Canada. Population: Women aged 18–49 years who were premenopausal and not pregnant were recruited into three cohorts: healthy women, WLWH and women with recurrent BV. Methods: Demographic and clinical data were collected via interviews and medical chart reviews. Vaginal swabs were collected for Gram‐stain assessment and microbiome profiling using the cpn 60 barcode sequence. Main outcome measures: To compare overall community composition differences, we used compositional data analysis methods, hierarchical clustering and Kruskal–Wallis tests where appropriate. Results: Clinical markers such as odour and abnormal discharge, but not irritation, were associated with higher microbial diversity. WLWH with unsuppressed HIV viral loads were more likely than other groups to have non‐ Gardnerella ‐dominated microbiomes. HIV was associated with higher vaginal microbial diversity and this was related to HIV viral load, with unsuppressed women demonstrating significantly higher relative abundance of Megasphaera genomosp. 1, Atopobium vaginae and Clostridiales sp. (all P < 0.05) compared with all other groups. Conclusions: In WLWH, unsuppressed HIV viral loads were associated with a distinct dysbiotic profile consisting of very low levels of Lactobacillus and high levels of anaerobes. Tweetable abstract: Vaginal microbiomes in WLWH with viral load >50 copies/ml have distinct dysbiotic profiles with high levels of anaerobes. Tweetable abstract: Vaginal microbiomes in WLWH with viral load >50 copies/ml have distinct dysbiotic profiles with high levels of anaerobes.